The early days of plastid retrograde signaling with respect to replication and transcription - Tanaka, Kan; Hanaoka, Mitsumasa (Frontiers in Plant Science, 2013)
The plastid signal was originally defined as a pathway that informs the nucleus of the chloroplast status and results in the modulation of expression of nuclear-encoded plastid protein genes. However, the transfer of chloroplast genes into the nuclear genome is a prerequisite in this scheme, although it should not have been established during the very early phase of chloroplast evolution. We recently demonstrated in a primitive red alga that the plastid-derived Mg-protoporphyrin IX (Mg-ProtoIX) activates nuclear DNA replication through the stabilization of a G1 cyclin, which coordinates the timing of organelle and nuclear DNA replication. This mechanism apparently does not involve any transcriptional regulation in the nucleus, and could have been established prior to gene transfer events. However, a retrograde signal mediating light-responsive gene expression may have been established alongside gene transfer, because essential light sensing and regulatory systems were originally incorporated into plant cells by the photosynthetic endosymbiont. In this short article, we discuss the origins, early days and evolution of the plastid retrograde signal(s).